# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+1\right ) y^{\prime \prime \prime }+9 x^{2} y^{\prime \prime }+18 x y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-x \right ) y^{\prime \prime }+\left (4 x +2\right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y \left (1-\ln \left (y\right )\right ) y^{\prime \prime }+\left (1+\ln \left (y\right )\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{x} = 0
\] |
✓ |
✓ |
|
\[
{}x \left (x +2 y\right ) y^{\prime \prime }+2 x {y^{\prime }}^{2}+4 \left (x +y\right ) y^{\prime }+2 y+x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+{y^{\prime }}^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-\frac {y^{\prime }}{x}+x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime \prime }+8 x y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime \prime }-\cos \left (x \right ) y^{\prime }+2 y \sin \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }-6 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+x^{\prime \prime } t = 1
\] |
✓ |
✓ |
|
\[
{}\frac {x^{\prime }+x^{\prime \prime } t}{t} = -2
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } = -\frac {x}{t^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } = \frac {4 x}{t^{2}}
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }+3 t x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } t +4 x^{\prime }+\frac {2 x}{t} = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }-7 t x^{\prime }+16 x = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }+3 t x^{\prime }-8 x = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }+t x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }-t x^{\prime }+2 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+t^{2} x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }-2 x = t^{3}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+\frac {x^{\prime }}{t} = a
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }-3 t x^{\prime }+3 x = 4 t^{7}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+t x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-t x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-\frac {\left (2+t \right ) x^{\prime }}{t}+\frac {\left (2+t \right ) x}{t^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }+t x^{\prime }+\left (t^{2}-\frac {1}{4}\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+4 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-10 x y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+6 x y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x y^{\prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-4 x^{2} y^{\prime \prime }+8 x y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right )^{2} y^{\prime \prime }-3 \left (1+x \right ) y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-x +1\right ) y^{\prime \prime }-\left (x^{2}+x \right ) y^{\prime }+\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x +1\right ) y^{\prime \prime }-4 \left (1+x \right ) y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}-x^{2}\right ) y^{\prime \prime }-\left (x^{3}+2 x^{2}-2 x \right ) y^{\prime }+\left (2 x^{2}+2 x -2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-6 x y^{\prime }+10 y = 3 x^{4}+6 x^{3}
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right )^{2} y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+2 y = 1
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+2 x \right ) y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+2 y = \left (x +2\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x \left (x +2\right ) y^{\prime }+\left (x +2\right ) y = x^{3}
\] |
✓ |
✓ |
|
\[
{}x \left (x -2\right ) y^{\prime \prime }-\left (x^{2}-2\right ) y^{\prime }+2 \left (x -1\right ) y = 3 x^{2} \left (x -2\right )^{2} {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}\left (2 x +1\right ) \left (1+x \right ) y^{\prime \prime }+2 x y^{\prime }-2 y = \left (2 x +1\right )^{2}
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right )^{2} y^{\prime \prime }-2 \sin \left (x \right ) \cos \left (x \right ) y^{\prime }+\left (\cos \left (x \right )^{2}+1\right ) y = \sin \left (x \right )^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{\prime \prime }-4 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}9 x^{2} y^{\prime \prime }+3 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+6 x y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-10 x y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-x^{2} y^{\prime \prime }-6 x y^{\prime }+18 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 4 x -6
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+8 y = 2 x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+4 x y^{\prime }+2 y = 4 \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 2 x \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 4 \sin \left (\ln \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }-10 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+5 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 y = 4 x -8
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = -6 x^{3}+4 x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x y^{\prime }-6 y = 10 x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+8 y = 2 x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-6 y = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x +2\right )^{2} y^{\prime \prime }-\left (x +2\right ) y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x -3\right )^{2} y^{\prime \prime }-6 \left (2 x -3\right ) y^{\prime }+12 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } t -2 x^{\prime }+9 t^{5} x = 0
\] |
✓ |
✓ |
|
\[
{}t^{3} x^{\prime \prime \prime }-3 t^{2} x^{\prime \prime }+6 t x^{\prime }-6 x = 0
\] |
✓ |
✓ |
|
\[
{}\left (t^{3}-2 t^{2}\right ) x^{\prime \prime }-\left (t^{3}+2 t^{2}-6 t \right ) x^{\prime }+\left (3 t^{2}-6\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}t^{3} x^{\prime \prime \prime }-\left (3+t \right ) t^{2} x^{\prime \prime }+2 t \left (3+t \right ) x^{\prime }-2 \left (3+t \right ) x = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }+3 t x^{\prime }+3 x = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 t +1\right ) x^{\prime \prime }+t^{3} x^{\prime }+x = 0
\] |
✗ |
✗ |
|
\[
{}t^{2} x^{\prime \prime }+\left (2 t^{3}+7 t \right ) x^{\prime }+\left (8 t^{2}+8\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}t^{3} x^{\prime \prime }-\left (t^{3}+2 t^{2}-t \right ) x^{\prime }+\left (t^{2}+t -1\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}t^{3} x^{\prime \prime }+3 t^{2} x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (t \right ) x^{\prime \prime }+\cos \left (t \right ) x^{\prime }+2 x = 0
\] |
✗ |
✓ |
|
\[
{}\frac {\left (t +1\right ) x^{\prime \prime }}{t}-\frac {x^{\prime }}{t^{2}}+\frac {x}{t^{3}} = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }+t x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}\left (t^{4}+t^{2}\right ) x^{\prime \prime }+2 t^{3} x^{\prime }+3 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-\tan \left (t \right ) x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}f \left (t \right ) x^{\prime \prime }+g \left (t \right ) x = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }+\left (t +1\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y^{\prime \prime }+\frac {\lambda y}{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y^{\prime \prime }+\frac {\lambda y}{x} = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+\left (x^{2}+1\right ) y^{\prime \prime }+\frac {\lambda y}{x^{2}+1} = 0
\] |
✓ |
✓ |
|
\[
{}-\frac {6 y^{\prime } x}{\left (3 x^{2}+1\right )^{2}}+\frac {y^{\prime \prime }}{3 x^{2}+1}+\lambda \left (3 x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x^{4} x^{\prime }-x^{\prime }+x = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }+x^{\prime }+{x^{\prime }}^{3}+x = 0
\] |
✗ |
✗ |
|